PENERAPAN PRINSIP ITIKAD BAIK PADA KLAIM ASURANSI JIWA KUMPULAN PADA PRUDENTIAL INDONESIA: Application of Good Faith Principle on Group Life Insurance Claims at Prudential Indonesia - Salsabila Usfa Xinamona; Suci Lestari Halim (Reformasi Hukum Trisakti, 2025)
Insurance is a legal agreement between two parties: the insurer and the insured. This study examines the application of the principle of utmost good faith in a group life insurance claim submitted by P.T. Sutomo Agrindo Mas on behalf on the late Mr. Martinus Rusmanto to P.T. Prudential Indonesia, as well as the insurer’s responsibility in the rejection of the claim. This research is normative in type, using a legal principle approuch, particularly focusing on the principle of good faith within life insurance law. The study is descriptive in nature, using secondary data supported by interviews, analyzed qualitatively, and concluded deductively. The result show that the principle of good faith was not upheld by the insured, who provided false information regarding his medical history in the Health Declaration Letter (SPAK), violatating Article 251 of the Indonesia Commercial Code. As a result, the insurer rightfully rejected the claim. The insurer’s responsibility was fulfilled by refunding the premiums to the policyholder, P.T. Sutomo Agrindo Mas, after deducting administrative fees, in accordance with Article 8 of Pru Work Life Policy No. 1000760.